The evaluation of cellular and humoral immunity characteristics in gastrointestinal and hepatocellular cancers - Türkdoğan, Mehmet Kürşad; Kızıltan, Huriye Şenay; Bayır, Ayşe Güneş; Özer, Ömer Faruk; Türkdoğan, Kürşad (Huriye Şenay Kızıltan, 2022)
BACKGROUND: Gastrointestinal (GI) cancers (Ca) are a global health problem leading to high mortality around the world. Human organism presents a perfect defense against cancers by immune system. In this study, we aimed to evaluate the characteristics of the humoral and cellular immune systems in GI Ca patients. MATERIALS AND METHODS: Cellular and humoral immune parameters (CD3, CD4, CD8, CD16/CD56 and CD19 lymphocytes) were investigated in the peripheral blood of advanced 198 GI and hepatocellular cancer (HCC) patients by flow cytometry. RESULTS: CD8 lymphocyte levels were significantly increased in pancreatic and colorectal Ca groups (p< 0.05) and natural killer (CD16/CD56) lymphocytes were also significantly higher in gastric Ca, colorectal Ca and HCC patients compared to the controls (p< 0.01-0.05). Besides, CD19 lymphocytes were significantly lower in the pancreatic and colorectal Ca groups (p<0.01-0.05). CD3 and CD4 lymphocyte levels were not significantly different in all cancer groups. CONCLUSİON: Cellular immunity did not weaken, even activated in the course of gastrointestinal carcinogenesis but, this activation seems insufficient in the fight against GI cancers. Also, we observed severe decline of humoral immunity parameters associated with the progress of carcinogenesis. Strengthening humoral immune system must be considered in the future strategy of the cancer immunotherapy. KEY WORDS: Gastrointestinal cancers, cellular and humoral immunity.
Keywords: Gastrointestinal cancers; Cellular and humoral immunity